Storynomics Strategy as Digital Branding of Digital Forests In Bukit Peramun, Belitung - Renanda, Alfiyyah Zalfah; Rahmanita, Myrza; Boediman, Surya Fadjar; Nurbaeti, Nurbaeti (Jurnal Toursci, 2025)
Background. Digital branding has emerged as a crucial element that not only expands the reach of tourism destinations but also forms a unique and attractive brand image. A consistent brand identity, packed with compelling stories, is an essential foundation for building a positive image that strengthens the attractiveness of the destination in the minds of the audience. Aims. This study aims to analyze the strategy of applying storynomics as a form of digital branding in the Bukit Peramun Digital Forest in Belitung. Methods. Using qualitative approaches and case study methods, as well as analysis based on the SOAR (Strengths, Opportunities, Aspirations, Results) framework, this study explores how story narratives are combined with digital technologies such as augmented reality (AR), QR codes, and social media to build immersive and interactive travel experiences. Result. The results of the study demonstrate that the application of storynomics can enhance the attractiveness of destinations through authentic, visual, and emotional storytelling. Storynomics successfully creates an emotional connection with visitors, strengthens the destination's brand identity, and increases traveller engagement and loyalty. Conclusion. The Bukit Peramun Digital Forest is considered to have successfully leveraged the power of storytelling to create a unique destination image in the digital era. This study concludes that storynomics is an effective strategy in supporting tourism digitalization, especially in building destination branding based on experience and emotional engagement. Implementation. The suggestions put forward emphasize the importance of collaboration between destination managers, local communities, and the private sector to consistently strengthen narrative content production, as well as to develop specialized training for destination managers to create relevant, creative, and educational stories